Scientific analysis of the Erkurgan historical and archeological complex in Karshi district of Kashkadarya region - Оdilova F.O; Maxmatqulov I.T (Genius Journals, 2022)
The article provides information about the archeological excavations at the site of the Erkurgan ruins near the city of Karshi, the historical formation of this object, which is important for the cultural life of the oasis, and its current state.
Keywords: Fortress; temple; fortress; mausoleum